A STUDY OF SOCIO-CENTRIC AND EGO-CENTRIC VALUES AMONG SENIOR SECONDARY SCHOOL STUDENTS IN ZARIA METROPOLIS: IMPLICATION FOR COUNSELLING - Bello, Raliya Muhammad (Sokoto Educational Review, 2011)
The purpose of this study was to investigate secondary school students’ acceptance of some socio-centric values (honesty, cooperation and justice) and egocentric values (dishonesty, uncooperativeness and injustice) and conflicts between the two (2) groups of values. 171 (88 males and 83 females) Students were randomly selected from fo u r (4) senior secondary schools in Zaria metropolis as the sample for the study Socio-centric and egocentric values scale (SEVS) designed by the researcher was used for the data collection. Three research questions were raised and answered using descriptive statistics (percentages). Results revealed that the respondents had a higher percentage of acceptance of the socio-centric values than the egocentric values. However, a comparison of the male’s and female’s responses showed that the male respondents had higher percentages of acceptance of both the Socio-centric and egocentric values and also had higher conflicts in the measured values than the female respondents. Based on these findings, more studies on values conflicts among adolescents and youth especially experimental studies with techniques of healthy values development was recommended.